Measuring the Digital Economy. (Policy Papers; Policy Paper ;, 2018)
Digitalization encompasses a wide range of new applications of information technology in business models and products that are transforming the economy and social interactions. Digitalization is both an enabler and a disruptor of businesses. The lack of a generally agreed definition of the 'digital economy' or 'digital sector' and the lack of industry and product classification for Internet platforms and associated services are hurdles to measuring the digital economy. This paper distinguishes between the 'digital sector' and the increasingly digitalized modern economy, often called the 'digital economy,' and focuses on the measurement of the digital sector. The digital sector covers the core activities of digitalization, ICT goods and services, online platforms, and platform-enabled activities such as the sharing economy.